Energy resource centres (ERCs) as vehicles for extracting higher benefits from solar power in rural and suburban areas of developing countries (the case of Uganda) - Mbalyohere, Charles; Aguti, Jessica; Nabushawo, Harriet (Open Impact Conference, 2019)
The very low access to energy in African countries, where over 70% of the population still live in the dark, is significantly hindering development (World Bank, 2019).1 While some progress has been made in recent years to improve access to traditional on-grid and new off-grid systems, the rate of change is low. The problem is particularly evident in rural and suburban areas where over 80% of the population are resident. A major barrier is that the understanding of the use of solar power systems has been left to the startup companies that offer the systems. In most cases, these companies are located far from the rural areas. Consequently, they are not well positioned to systematically investigate solar usage patterns of their customers. The loophole in turn weakens the capability of these firms to develop suitable training and effective customer care services (Amankwah-Amoah, 2015). It has further hindered the capability of these firms to develop products and services that are more strongly adapted to local needs. The potential for value-added use not only in homes, but also for farming, entrepreneurship and broader income-generating activities, has hence remained largely unexploited. Key economic activity like farming and rural/suburban entrepreneurship has as a result not benefited from solar power to the extent that would have been needed to accelerate development.